ANALYSIS OF COOPERATIVE HEALTH LEVEL ON KOPWAN MEKAR KENANGA TULUNGAGUNG YEAR 2019 – 2021 - Queentantry Anne Rose; RN Ayuanti; E Syahputra (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2022)
Thiszstudy aims to explain the influence of changes in digitalization and interpersonal communication on employee performance at PT. Galaxy Purbaya Sakti Kediri. This research is a quantitativeZtypeZofzcausalzassociative research, the sampling technique used is a saturated sample, andzaztotalzofz40zsampleszwereztakenzfromzthe entire population at PT. Galaxy Purbaya Sakti Kediri. Research data were obtained based on interviews, observations, and questionnaires. The analysis technique used is using Validity Test, Reliabilityztest,zClassiczAssumptionztest, multiplezlinearzAnalysis, t-test (partial), F test (simultaneous), and Coefficient of Determination (R2). The results of the research that has been carried out are obtained by multiple linear equations, namely Y = 6.832+0.154X1+0.210X2+e. The results of the t-test variable for Digitalization Change (X1) show a significance of 0.168> 0.050, meaning that the Digitalization Change has no significant effect on employee performance, the results of the variable t-test Interpersonal Communication (X2) show a significance of 0.010 <0.050 meaning that Interpersonal Communication does not have a significant effect on employee performance, and the F test results show a significance of 0.001 <0.050 meaning that Changes in Digitization (X1) and Interpersonal Communication (X2) have a significant effect on Employee Performance at PT. Galaxy Purbaya Sakti Kediri